Exceptional preservation of reidite in the Rochechouart impact structure, France: New insights into shock deformation and phase transition of zircon. (19th August 2021) - Plan, Anders; Kenny, Gavin G.; Erickson, Timmons M.; Lindgren, Paula; Alwmark, Carl; Holm‐Alwmark, Sanna; Lambert, Philippe; Scherstén, Anders; Söderlund, Ulf
Abstract: Reidite, the high‐pressure zircon (ZrSiO4 ) polymorph, is a diagnostic indicator of impact events. Natural records of reidite are, however, scarce, occurring mainly as micrometer‐sized lamellae, granules, and dendrites. Here, we present a unique sequence of shocked zircon grains found within a clast from the Chassenon suevitic breccia (shock stage III) from the ˜200 Ma, 20–50 km wide Rochechouart impact structure in France. Our study comprises detailed characterization with scanning electron microscopy coupled with electron backscatter diffraction with the goal of investigating the stability and response of ZrSiO4 under extreme P–T conditions. The shocked zircon grains have preserved various amounts of reidite ranging from 4% up to complete conversion. The grains contain various variants of reidite, including the common habits: lamellae and granular reidite. In addition, three novel variants have been identified: blade, wedge, and massive domains. Several of these crosscut and offset each other, revealing that reidite can form at multiple stages during an impact event. Our data provide evidence that reidite can be preserved in impactites to a much greater extent than previously documented. We have further characterized reversion products of reidite in the form of fully recrystallized granular zircon grains and minute domains of granular zircon in reidite‐bearing grains that occur in close relationship to reidite. Neoblasts in these grains have a distinct crystallography that is the result of systematic inheritance of reidite. We interpret that the fully granular grains have formed from prolonged exposure of temperatures in excess of 1200 °C. Reidite‐bearing grains with granular domains might signify swift quenching from temperatures close to 1200 °C. Grains subjected to these specific conditions therefore underwent partial zircon‐to‐reidite reversion, instead of full grain recrystallization. Based on our ZrSiO4 microstructural constraints, we decipher the grains evolution at specific P–T conditions related to different impact stages, offering further understanding of the behavior of ZrSiO4 during shock.